Shear bond strength of amalgam to dentin using different dentin adhesive systems - Farimah Sardari; Marjaneh Ghavam Nasiri; Nasrin Amini; Berahman Sabzevari (Tehran University of Medical Sciences, 2012)
Background and Aims: The aim of this in vitro study was to assess the shear bond strength of amalgam to dentin using four dentin adhesive systems.Materials and Methods: One hundred human molars were selected. After enamel removal, a dentin cylinder with 3 mm thickness was prepared. Eighty specimens were resorted with amalgam and four dentin adhesive systems as follows (n=20): group 1, Scotch Bond Multi-Purpose; group 2, One Coat Bond; group 3, PQ1; and group 4, Panavia-F. In group 5, 20 specimens were resorted with amalgam and varnish as control group. The specimens were incubated at 37°C for 24 h. The shear bond strengths were then measured by using push out method. The data were analyzed by one-way ANOVA and post hoc Duncan's tests.Results: Mean values for bond strengths of test groups were as follows: group 1=21.03±8.9, group 2=23.47±9, group 3=13.16±8.8, group 4=20.07±8.9 and group 5=14.15±8.7 MPa±SD. One-way ANOVA showed the statistically significant difference between the bond strengths of five groups (P=0.001). Post hoc Duncan's test showed significant difference between groups 1and 3 (P=0.008), groups 1 and 5 (P=0.019), groups 2 and 5 (P=0.0008), groups 4 and 5 (P=0.042), and groups 3 and 4 (P=0.018).Conclusion: Results of this study showed that the bond strength of amalgam to dentin using One Coat Bond as dentin adhesive system was higher than that observed in other dentin adhesive systems.